2001
DOI: 10.1071/ea99104
|View full text |Cite
|
Sign up to set email alerts
|

Effects of phosphonate and salicylic acid treatments on anthracnose disease development and ripening of 'Kensington Pride' mango fruit

Abstract: This study investigated treatment of mango (Mangifera indica L.) fruit with 2 host defence-promoting compounds for suppression of anthracnose disease (Colletotrichum gloeosporioides). Cultivar ‘Kensington Pride’ fruit were treated at concentrations of up to 1000 mg/L with either potassium phosphonate or salicylic acid. Applications were by various combinations of pre- and postharvest dips and vacuum infiltration. Postharvest treatments at up to 2000 mg/L salicylic acid were evaluated in a second fruiting seaso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0
4

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 68 publications
(36 citation statements)
references
References 33 publications
1
31
0
4
Order By: Relevance
“…Studies have shown that SA treatment can enhance disease resistance of a few growing plants or detached plant organs (Sticher et al, 1997;Meena et al, 2001;Zainuri et al, 2001;Qin et al, 2003). Our study indicated that postharvest disease resistance of Ya Li pear fruit could also be notably enhanced by foliar SA sprays on the trees during the growth season.…”
Section: Discussionsupporting
confidence: 43%
See 2 more Smart Citations
“…Studies have shown that SA treatment can enhance disease resistance of a few growing plants or detached plant organs (Sticher et al, 1997;Meena et al, 2001;Zainuri et al, 2001;Qin et al, 2003). Our study indicated that postharvest disease resistance of Ya Li pear fruit could also be notably enhanced by foliar SA sprays on the trees during the growth season.…”
Section: Discussionsupporting
confidence: 43%
“…SA is a simple phenolic compound naturally produced by many plants and has been considered as a signal molecule in the signal transduction pathway in plants (Malamy et al, 1990;Sticher et al, 1997). A few studies have shown that disease resistance in fruit could also be induced by postharvest treatment with SA (Qin et al, 2003;Zainuri et al, 2001). It has been demonstrated that pre-harvest application of SA tended to suppress postharvest anthracnose disease severity caused by Colletotrichum gloeosporioides in mango fruit (Zainuri et al, 2001), and that application of acibenzolar-S-methyl, a functional analogue of SA, on melon plant prior to flowering could effectively inhibit infections of several postharvest fungal diseases in melon fruit (Huang et al, 2000).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…The use of various chemical, physical and biological elicitors can artificially induce host resistance (Wilson et al 1994). The exogenous application of salicylic acid (SA), which is involved in the disease resistance in plants, has been demonstrated to be effective in enhancing the disease resistance in mango fruit (Zainuri et al 2001;Zeng et al 2006). The post-harvest application of SA at 2000 ppm concentration in 'Kensington' mangoes reduced the severity of anthracnose, but doses up to 1000 ppm were not very effective (Zainuri et al 2001).…”
Section: Other Approachesmentioning
confidence: 99%
“…The exogenous application of salicylic acid (SA), which is involved in the disease resistance in plants, has been demonstrated to be effective in enhancing the disease resistance in mango fruit (Zainuri et al 2001;Zeng et al 2006). The post-harvest application of SA at 2000 ppm concentration in 'Kensington' mangoes reduced the severity of anthracnose, but doses up to 1000 ppm were not very effective (Zainuri et al 2001). The vacuum infiltration of 1 mmoll −1 SA in 'Matisu' mango also enhanced the disease resistance against anthracnose by increasing the activities of phenylalanine ammonia lyase (PAL) and b-1,3-glucanase in SA-treated fruit (Zeng et al 2006).…”
Section: Other Approachesmentioning
confidence: 99%